Flow diversion treatment for giant intracranial serpentine aneurysms - Tong, Xin; He, Zijun; Han, Mingyang; Feng, Xin; Duan, Chuanzhi; Liu, Aihua (Frontiers in Aging Neuroscience, 2022)
Background Giant serpentine aneurysms (GSAs) are among the most complex and challenging type of intracranial aneurysms. Surgical clipping, bypass, or endovascular parent artery occlusion has been the main treatment of GSAs in the past. However, studies on flow diversion (FD) are limited. Therefore, we reported our experience with patients with GSAs treated with FD. Methods Patients with GSAs treated with FD from 2012 to 2020 in our single center were retrospectively reviewed. Angiographic outcomes were graded according to the O’Kelly–Marotta scale as complete occlusion (D), trace filling (C), entry remnant (B), or aneurysm filling (A). Clinical outcomes were assessed using the modified Rankin scale (mRS) score. We also collected the patients’ treatment details and perioperative complications. Results Thirteen patients with 14 aneurysms were included, including three in the anterior circulation and 11 in the posterior circulation. Grades B–D were found in 72.7% (8/11) of the GSAs. Good prognosis (mRS score, 0–2) was found in 66.7% (8/12) and 50.0% (6/12) of the patients at the 6-month and latest follow-up, respectively. Parent artery occlusion was found in three cases of GSAs. Five postoperative complications were observed, including two minor complications and three major complications. Conclusion Although reconstructive treatment with FD could be considered as one of the treatment strategies for patients with both anterior and posterior circulation GSAs, however, the risk of complications and parent artery occlusion should be considered.